Architectural and Artistic Organization of the Facades of Modern Buildings in Historical Cities (On the Example of Samarkand City) - H. H. Juraev; J. H. Kadyrov (International Journal on Integrated Education, 2022)
This scientific article discusses the national architectural monuments, residential buildings, architectural elements and artistic decorations, the formation of the architectural and artistic environment, in particular, the oriental style of decoration, which was formed in ancient times in Samarkand and has survived to the present day